Pengaruh Pertumbuhan Ekonomi Dan Inflasi Terhadap Kemiskinan Di Provinsi Kalimantan Utara - Syaifullah, Mahfud; Nur, Adi Aspian (STIE Jambatan Bulan, 2023)
The objectives in this study are 1. Knowing that economic growth can have an effect on changes in reducing poverty rates in North Kalimantan Province 2. Knowing that inflation can have a changing effect in increasing the poverty rate in North Kalimantan Province. Using method Multi Regression Analysis. The results of this study are, 1.The level of welfare is related to the level of poverty, if the level of welfare of the community is low then the level of poverty is also high and if the level of welfare is high then the level of poverty will be low. 2. The use of inflation variables because inflation is a continuous increase in the price of general goods over a long period of time, the increase in the price of goods if left continuously will affect the decline in people's purchasing power. The decline in people's purchasing power is due to people's inability to buy these goods or low income. The conclusions in this study are as follows: 1. Economic growth can have an effect on changes in reducing poverty rates in North Kalimantan province. 2. Inflation can have a changing effect in increasing the poverty rate in North Kalimantan province.